Matching school sports managers' job demands with resources for optimal performance in Nigeria - Ufuoma Vivian Arenyeka; Dorah Ataphia Akporehe; Ochuko Eric Nabofa (Universidad de Murcia, 2024)
School sports are beneficial to schools, communities and society as a whole in that they can prevent delinquent behaviours, force commitment to rules, promote social control and teach societal/school values, among others. Deriving these benefits of school sports requires the optimal performance of school sports managers, who teach physical and health education (PHE) as a subject, games masters, house masters, head teachers and seconded school coaches. In this literature review, the JD-R theory was used to explore the literature regarding several potential job demands and job resources within the school sports management environment and how these can be matched for the optimum performance and productivity of school sports managers. It was established that there is a need to identify all possible physical, psychological, social or organizational demands and resources in school sports management to achieve optimal performance in school sports management. The JD-R literature suggests that organizations need to offer employees sufficient job challenges and resources, including feedback, social support, and skill variety, for optimal productivity.